Development of interactive powerpoint learning media based on contextual to improve student learning outcomes on volume materials - Shintya Eka Rosalia Putri; Erwin Putera Permana; Rian Damariswara (Jurnal Pijar Mipa, 2023)
This research is being carried out after observations and interviews at SDN Kraton, there is a problem that students need better learning outcomes. It's due to the need for more media for the learning process; the learning resources are only student books and lecture methods. So, it is necessary to develop the media to support the learning process with the hope of maximum learning outcomes. Applying actual concepts to learning mathematics in everyday life relates to contextual approaches. In reality, in everyday life, mathematics plays a vital role. This research aims to develop a contextual-based interactive PowerPoint learning medium to improve student's learning outcomes in the V class of SDN Kraton. This development research uses the ADDIE model development modes. This research's subject is the SDN Kraton V class, with 18 students. This product passes through the validation stage of the material expert, the media validation test, the elevation response of students and teachers, and the pretest-postest. The validation test obtained an 87.5% score with valid criteria. The media expert's validation gets an 80% acquisition with a very valid criterion. Student response scores a percentage score of 83.33% with highly practical criteria, and teacher response gains a 90% achievement with highly pragmatic criteria. The product test was declared effective by increasing the pretest to the posttest with an average of 0.7 over the average criteria. So, the use of learning media can enhance student learning outcomes.